Coherent fusion of water array and protonated amine in a metal-sulfate-based coordination polymer for proton conduction - Manna, Biplab; Anothumakkool, Bihag; Desai, Aamod V.; Samanta, Partha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2015)
A new function of metal-sulfate-based co-ordination polymer (CP) for proton,conduction Was investigated through rational integration of a continuous water array and protonated amine in the coordination space of the CP. The H-bonded arrays of watet molecules along with nitrogen-rich aromatic cation (protonated melamine) facilitate proton conduction in the compound under humid conditions. Although several reports of metal-oxalate/phosphate-based CPs showing proton conduction are known, this is the first designed synthesis of a metal sulfate-based CP bearing-Water arrays functioning as a solid-state proton conductor: